Coupler Energy Absorption Schemes for 4-vehicle Formation Coupled Metro Train - DONG Yanbing (Chengshi guidao jiaotong yanjiu)
[Objective] The coupler buffer energy absorption system is a key part in the overall energy absorption system of metro trains, having significant influence on train safety and comfort. By analyzing the energy absorption performance of couplers in collision for different configuration schemes of 4-vehicle formation coupled trains, theoretical basis and technical support is provided for the coupler design. [Method] Different coupler energy absorption configuration schemes are proposed. Using 4-vehicle formation coupled metro train as research object, simulation calculation methods are employed to model collision scenarios at different train speeds and obtain the characteristic energy absorption curves of couplers. By comparing and analyzing the variations in these energy absorption curves across different configuration schemes, the advantages and disadvantages of each energy absorption scheme are evaluated. [Result & Conclusion] Different coupler energy absorption configuration schemes show significant differences in performance during train collisions. Considering both the energy absorption effectiveness and the train operational safety on the basis of actual train operational requirements, the optimal coupler configuration scheme suitable for 4-vehicle formation coupled metro train is proposed.